The endothelial transcription factor ERG mediates Angiopoietin-1-dependent control of Notch signalling and vascular stability - Shah, A. V. (Nat Commun, 2017)
Notch and Angiopoietin-1 (Ang1)/Tie2 pathways are crucial for vascular maturation and stability. Here we identify the transcription factor ERG as a key regulator of endothelial Notch signalling. We show that ERG controls the balance between Notch ligands by driving Delta-like ligand 4 (Dll4) while repressing Jagged1 (Jag1) expression. In vivo, this regulation occurs selectively in the maturing plexus of the mouse developing retina, where Ang1/Tie2 signalling is active. We find that ERG mediates Ang1-dependent regulation of Notch ligands and is required for the stabilizing effects of Ang1 in vivo. We show that Ang1 induces ERG phosphorylation in a phosphoinositide 3-kinase (PI3K)/Akt-dependent manner, resulting in ERG enrichment at Dll4 promoter and multiple enhancers. Finally, we demonstrate that ERG directly interacts with Notch intracellular domain (NICD) and β-catenin and is required for Ang1-dependent β-catenin recruitment at the Dll4 locus. We propose that ERG coordinates Ang1, β-catenin and Notch signalling to promote vascular stability.